The Morality of Health Care Reform: Liberal and Conservative Views and the Space between Them - Stoltzfus Jost, Timothy (The Hastings Center report, 2017)
We have just completed an exhausting nine-month debate on the future of the Affordable Care Act. I see this debate as having ended—as of this writing—in a draw. After months of repeal efforts, Republicans in the House barely passed in early May, with a 217-to-213 margin, the American Health Care Act, which would have significantly amended the ACA. Republicans in the Senate spent the summer trying to arrive at amendments to the AHCA that could attract fifty of their fifty-two votes, but in the end, the clock ran out on their opportunity to enact an amendment without Democratic input. With this legislative failure, we appear to be in a stalemate. The Affordable Care Act remains in place as the law of the land, but the Trump administration seems committed to at best condemning the ACA to malign neglect and at worst actively undermining it at every opportunity. Given the political stalemate, the time is right to reassess the deeper issues at stake and ponder the prospects for a considered compromise on health reform.